Performance of vertically-placed stiffened corrugated panels in steel plate shear walls: Shear elastic buckling analysis. (15th June 2023) - Feng, Lifei; Yang, Hanwen; Sun, Tianshu; Ou, Jinping
Abstract: Adding horizontal stiffeners to vertically-placed corrugated panels is an effective way to improve their shear buckling strength. Since the shear elastic buckling loads ( N cr ) of vertically-placed stiffened corrugated steel walls (VSCSWs) are related to their practical design, this study investigates the VSCSWs' shear elastic buckling behaviors and aims to determine the formulas for predicting the N cr of VSCSWs. Firstly, the number of horizontal stiffeners required by VSCSWs is discussed utilizing the calculation model of VSCSWs' shear elastic buckling load established based on the minimum potential energy and the Ritz method. Then, the shear elastic buckling behaviors of VSCSWs with one pair and two pairs of horizontal stiffeners are analyzed, and formulas for predicting their shear elastic buckling coefficients are proposed. Lastly, finite element shear elastic buckling analyses are conducted to verify the accuracy of the proposed formulas. It is found that the shear elastic buckling coefficient of VSCSWs first grows and then almost remains unchanged with the increased rigidity ratio of the stiffening system. It has been observed that the equations proposed are in good agreement with the numerical results and can be applied to the design of the VSCSWs. Highlights: The required number of horizontal stiffeners for vertically-placed corrugated panels is discussed and determined. Shear elastic buckling behaviors of vertically-placed stiffened corrugated steel walls (VSCSWs) are investigated. Formulas are proposed for predicting the shear elastic buckling loads of VSCSWs. The proposed formulas are validated by finite element numerical results.